Top of the techno list. (Bookseller, 2002)
Presents several books on computers. 'At Home With Computers,' by Elaine Lally; 'The Mechanical Turk,' by Tom Standage; 'Free As in Freedom: Richard Stallman and the Free Software Foundation,' by Sam Williams; 'Java in a Nutshell,' by David Flanagan.